2011
DOI: 10.1007/s12094-011-0674-1
|View full text |Cite
|
Sign up to set email alerts
|

The EORTC information questionnaire, EORTC QLQ-INFO25. Validation study for Spanish patients

Abstract: The EORTC QLQ-INFO 25 is a reliable and valid instrument when applied to a sample of Spanish cancer patients. These results are in line with those of the EORTC validation study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 28 publications
3
20
1
12
Order By: Relevance
“…For instance, a study on cancer patients observed age and gender not to be related to QoL [5]. In contrast, few studies detected differences in QoL in relation to age [31][32][33] and gender [31]. The difference in OHRQoL between the genders might be due to the difference in influences during the life course [34].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, a study on cancer patients observed age and gender not to be related to QoL [5]. In contrast, few studies detected differences in QoL in relation to age [31][32][33] and gender [31]. The difference in OHRQoL between the genders might be due to the difference in influences during the life course [34].…”
Section: Discussionmentioning
confidence: 99%
“…(7,8) One form of clinical, diagnostic and social approach is to use adapted scales and questionnaires. (9) To assess the amount of information the patients with different types of cancer receive during the phases of the diagnosis and treatment process, as well as for clinical and research purposes, the Quality of Life Group of the European Organization for Research and Treatment of Cancer (EORTC) developed the QLQ INFO 25 questionnaire, (10,11) which was validated for the Brazilian context by Monique Silva Carvalho concerning the semantic equivalence; and by Claudia Fernandes Rodrigues concerning the test-retest reliability (unpublished).…”
Section: Introductionmentioning
confidence: 99%
“…Polish doctors seem to shy away from informing the patients of the diagnosis and treatment options, finding it easier to talk to the family, which often leaves them with a feeling of guilt and helplessness. This attitude has been recently changing, also in other European countries, especially among younger professionals, although communication skills are not included in postgraduate medical training (Arraras et al 2011; Bracci et al 2008; Degner et al 1998; Kotlinowska and Wilusz 2010). There is a need to adapt shared information depending on the recipient (eg.…”
Section: Introductionmentioning
confidence: 99%
“…However, the existing ones are focused mainly on patients’ satisfaction or needs (Arraras et al 2011; Bonevski et al 2000; Degner et al 1998; Mesters et al 2001; Thomas et al 2004). …”
Section: Introductionmentioning
confidence: 99%